INHIBITORY EFFECT OF CHITOSAN OLIGOSACCHARIDE ON HUMAN HEPATOMA CELLS IN VITRO - Liu, Likun; Yi, Xin; Liu, Jia; Zhang, Ershao; Weiling, Li (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Chitosan oligosaccharide, the degradation products of chitin, was reported to have a wide range ofphysiological functions and biological activities. In this study, we explored the inhibitory effect of Chitosanoligosaccharide on human hepatoma cellsMaterials and Methods: MTT assay was applied to detect cell viability of the human hepatoma cells treated withChitosan oligosaccharide. Flow cytometric analysis was used to investigate the apoptosis of the human hepatoma cellstreated with Chitosan oligosaccharide. We employed western blot to investigate the underlying mechanisms involved inthe apoptosis.Results: Our data indicated that chitosan oligosaccharide dose-dependently inhibited the growth of hepatoma cells andinduced apoptosis. On the molecular level, chitosan oligosaccharide decreased Bcl-2 and increased Caspase-3expression which may be related to the apoptosis of hepatoma cells.Conclusion: Our results provide an experimental basis for the clinical development of Chitosan oligosaccharide as anovel anti-hepatoma drug.